Analisis Kesuksesan Sistem Informasi Manajemen Daerah (SIMDA) dengan Metode Delone dan Mclean Success Model dan Technology Acceptance Model (TAM) - Arie Vatresia; Tini Pasaribu (Diponegoro University, 2023)
Eight years since the implementation of the Regional Management Information System (SIMDA), there has been no specific research to analyze the information system both in terms of implementation, system quality, user acceptance, and the success of the system in its implementation. This study aims to determine the success of implementing the program at the Bengkulu Provincial DPMD office using the DeLone And McLean IS Success Model and Technology Accepeance Model (TAM) with seven research variables (system quality, information quality, perceived usefulness, perceived ease of use, service quality, user satisfaction, and net benefits). Furthermore, this research provides recommendations that can be used to update SIMDA so that it suits user needs. The seven variables of this study resulted in twelve proposed hypotheses (six were rejected and another was accepted). Six paths of accepted hypothetical relationships are: system quality with ease of use; relationship between information quality and perceived usefulness; relationship between information quality and net benefits; relationship between service quality and perceived ease of use; relationship between perceived ease of use and user satisfaction; and relationship between perceived usefulness and user satisfaction. Meanwhile, the relationship path of the rejected hypotheses is the relationship between system quality and perceived usefulness, the relationship between system quality and net benefits, the relationship between information quality and perceived ease of use, the relationship between service quality and user satisfaction, the relationship between perceived ease of use and perceived usefulness, and the relationship between user satisfaction and net benefits.